Feeding the hungry : advocacy and blame in the global fight against hunger - Jurkovich, Michelle, 1983- (Cornell University Press, 2020)
"This book investigates barriers to advocacy around a critical economic and social right-the right to food-and in so doing challenges dominant understandings of the relationships between human rights, norms, and law"--